High-load lignin-derived carbon / Ni3ZnC0.7 / ZnO / Ni ternary heterojunction composite material as well as preparation and application thereof
By using lignin as a surfactant and carbon source, a high-load lignin-derived carbon/Ni3ZnC0.7/ZnO/Ni ternary heterojunction composite material was prepared, which solved the problems of complex preparation process, high cost and poor catalytic stability in the prior art, and achieved efficient and economical improvement of catalytic performance.
Patent Information
- Application Number
- CN202411788940.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing Ni3ZnC0.7/ZnO/Ni ternary heterojunction composite materials have complex processes and high costs during the preparation process. The Ni3ZnC0.7 is poor under catalytic reaction conditions, making it difficult to optimize the balance between the various components to achieve the highest efficiency.
Using lignin as the surface ionic active agent and carbon source, a high-load lignin-derived carbon/Ni3ZnC0.7/ZnO/Ni ternary heterojunction composite was prepared by a two-step calcination under high temperature conditions. Lignin not only provides a carbon source and surfactant, but also disperses metal particles in synthesis, improving the structural stability and catalytic capacity of the catalyst.
The preparation process is simplified, the cost is reduced, the structural stability and catalytic performance of composite materials are improved, and its application efficiency in the field of photothermal catalysis is enhanced.
Smart Images

Figure CN119657187A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic / inorganic hybrid composite materials, and specifically relates to a high-load lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni ternary heterojunction composite material and its preparation and application Background Art
[0002] Faced with increasingly depleted fossil fuels and escalating environmental problems, the search for sustainable and renewable energy has become a serious global challenge. Among various potential alternative energy sources, hydrogen stands out as a clean and efficient energy carrier that is expected to significantly reduce greenhouse gas emissions. However, the production of hydrogen has traditionally relied on energy-intensive and carbon-emitting processes. Photothermal catalysis has emerged as an environmentally friendly, green and efficient method that uses solar energy to drive chemical reactions for hydrogen production. This technology exploits the ability of certain materials to absorb light and convert it into heat energy, thereby promoting endothermic reactions. In this context, lignin carbon-based materials and cellulose, two of the most abundant biopolymers on earth, have attracted much attention due to their potential role in improving the efficiency and sustainability of photothermal catalytic processes.
[0003] Nickel and zinc play a key role in photothermal catalytic hydrogen production. Nickel improves catalytic efficiency through its excellent hydrogen adsorption properties, while zinc improves stability and light absorption capacity, thereby increasing overall productivity. Their synergistic effect optimizes reaction conditions, making it an ideal choice for sustainable energy solutions.
[0004] Ni3ZnC 0.7 / ZnO / Ni ternary heterojunction composite materials have great potential in photothermal catalytic hydrogen production by utilizing their unique electronic properties and stronger light absorption ability. However, challenges still exist, such as the high cost and complexity of the preparation process. Under the catalytic reaction conditions, Ni3ZnC 0.7 The poor stability and easy deactivation of ternary heterojunction composites make it difficult to optimize the balance between the components to achieve the highest efficiency. Solving these problems is crucial to promote their practical application in the field of sustainable hydrogen energy.
[0005] Lignin is a complex aromatic polymer that is the main component of plant secondary cell walls and plays a key role in providing mechanical strength and resisting microbial invasion. Despite its abundance, lignin has not been fully utilized and is mainly regarded as a waste product in the papermaking industry. However, recent advances in materials science and biorefining processes have revealed the potential of lignin as a valuable resource. The structure of lignin is rich in aromatic rings and hydroxyl groups, making it very suitable for conversion into carbon-based materials with excellent photothermal properties. These lignin-derived carbon materials have excellent light absorption and thermal conductivity, making them ideal candidates for photothermal catalysis. Lignin-derived carbon can provide sufficient sites for catalyst loading due to its large specific surface area, supporting the catalyst to form a carrier effect. At the same time, the high degree of graphitization of lignin carbon can improve the electron transfer, stability, selectivity and active site efficiency of the composite material, thereby enhancing the overall catalytic performance of the composite material. By converting lignin into such functional materials, not only can the originally wasted resources be valued, but it also paves the way for sustainable hydrogen production methods using the inherent properties of biomass. Summary of the invention
[0006] In order to overcome the above-mentioned Ni3ZnC 0.7 / ZnO / Ni has complex process and high cost in the preparation process, and it is difficult to maintain Ni3ZnC under catalytic reaction conditions. 0.7 Structural stability (easy to deactivate) and optimization of Ni3ZnC 0.7 The primary purpose of the present invention is to provide a high-load lignin-derived carbon / Ni3ZnC 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material.
[0007] The present invention uses lignin as a surfactant and a carbon source, and prepares lignin-derived carbon / Ni3ZnC with different proportions, high loading and high catalytic performance by calcining at high temperature in a two-step method. 0.7 / ZnO / Ni ternary heterojunction composite material. Lignin not only provides a carbon source but also serves as a surfactant for the solution; at the same time, it plays a role in dispersing metal particles during synthesis; carbon loading broadens the light absorption range of the composite material, increases the specific surface area, plays a carrier and support role, and improves the structural stability and catalytic ability of the catalyst. This process has the advantages of simplicity, easy availability of raw materials, and low cost.
[0008] Another object of the present invention is to provide a lignin-derived carbon / Ni3ZnC prepared by the above preparation method. 0.7 / ZnO / Ni ternary heterojunction composite materials.
[0009] Another object of the present invention is to provide the above-mentioned lignin-derived carbon / Ni3ZnC 0.7 Application of / ZnO / Ni ternary heterojunction composite materials.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] Lignin derived carbon / Ni3ZnC 0.7 A method for preparing a ZnO / Ni ternary heterojunction composite material comprises the following steps:
[0012] (1) The lignin alcohol solution and the mixed salt solution of zinc salt and nickel salt are mixed evenly, the precipitant solution is added dropwise, and then water is added, heated for reaction, washed, and dried to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni ternary heterojunction composite material precursor;
[0013] (2) Lignin-derived carbon / Ni3ZnC 0.7 The precursor of the ternary heterojunction composite material is calcined to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni ternary heterojunction composite materials.
[0014] Preferably, in step (1), the ratio of lignin, zinc salt and nickel salt is 1.5-2.5 g: 5-10 mmol: 5-10 mmol; more preferably 2 g: 5-10 mmol: 5-10 mmol; most preferably 2 g: 10 mmol: 10 mmol.
[0015] Preferably, in step (1), the molar ratio of the precipitant, the zinc salt and the nickel salt is 5-8:0.5-2:0.5-2; more preferably 7-8:0.5-1:0.5-1; most preferably 8:1:1.
[0016] Preferably, the lignin in step (1) is at least one of alkali lignin, sulfate lignin, lignin sulfonate and enzymatic lignin; more preferably, it is alkali lignin.
[0017] Preferably, the concentration of the lignin alcohol solution in step (1) is 12.5 to 62.5 mg / mL; more preferably 37.5 to 62.5 mg / mL; most preferably 37.5 to 50 mg / mL.
[0018] Preferably, the alcohol solvent in the lignin alcohol solution in step (1) is anhydrous ethanol.
[0019] Preferably, the concentration of the mixed salt solution of zinc salt and nickel salt in step (1) is 0.5-1 mol / L; more preferably 0.75-1 mol / L; most preferably 1 mol / L.
[0020] Preferably, the zinc salt in step (1) is at least one of zinc nitrate, zinc acetate, zinc carbonate, zinc chloride and zinc oxalate; more preferably zinc nitrate.
[0021] Preferably, the nickel salt in step (1) is at least one of nickel nitrate, nickel acetate, nickel carbonate and nickel chloride; more preferably nickel nitrate.
[0022] Preferably, the precipitant solution in step (1) is at least one of aqueous ammonia, potassium hydroxide solution and sodium hydroxide solution; more preferably sodium hydroxide solution; the concentration of the precipitant solution is 5 to 9 mol / L; further preferably 5 to 8 mol / L; most preferably 7 to 8 mol / L.
[0023] Preferably, the volume ratio of the water added in step (1) to the precipitant solution is (0-80):10, and the volume of water is not 0; more preferably, it is (15-30):10; and most preferably, it is 30:10.
[0024] Preferably, the temperature of the heating reaction in step (1) is 60-100° C., and the time is 40-120 min; more preferably, the temperature of the heating reaction is 80-90° C., and the time is 60-120 min.
[0025] Preferably, the washing in step (1) refers to washing the mixed solution of the heated reaction products with deionized water and anhydrous ethanol after centrifugation; more preferably, washing with deionized water and anhydrous ethanol 1 to 5 times each.
[0026] Preferably, the drying in step (1) is conventional drying.
[0027] Preferably, the calcination temperature in step (2) is 450-550°C, more preferably 500-550°C, most preferably 550°C; the calcination time is 1-3h, most preferably 1h.
[0028] Preferably, the heating rate of the calcination in step (2) is 1 to 10°C / min; more preferably 3 to 6°C / min; most preferably 5°C / min.
[0029] Preferably, the calcination atmosphere in step (2) is at least one of nitrogen, ammonia and air; preferably nitrogen.
[0030] A lignin-derived carbon / Ni3ZnC prepared by the above preparation method 0.7 / ZnO / Ni ternary heterojunction composite materials.
[0031] The above-mentioned lignin-derived carbon / Ni3ZnC 0.7 Application of / ZnO / Ni ternary heterojunction composite materials in the field of photothermal catalysis.
[0032] Preferably, the application is photothermal catalytic reforming of cellulose to produce hydrogen.
[0033] More preferably, the method for photothermal catalytic reforming of cellulose to produce hydrogen is: lignin-derived carbon / Ni3ZnC 0.7 The mass ratio of the ZnO / Ni ternary heterojunction composite material to the substrate is 1:5-15; the temperature of the catalytic reaction is 453-493K.
[0034] More preferably, the substrate comprises ethanol and cellulose, wherein the mass ratio of ethanol to cellulose is 5 to 15:1.
[0035] The present invention provides a lignin-derived carbon / Ni3ZnC prepared by the above method 0.7 / ZnO / Ni ternary heterojunction composite material, the composite material has the advantages of good stability, rich pore volume and pore size, large specific surface, strong catalytic effect, etc., and is applied to the field of photothermal catalysis, especially in the research of photothermal catalytic reforming of cellulose to produce hydrogen, which can significantly improve its photothermal catalytic performance. 0.7 / ZnO / Ni can make up for the Ni3ZnC 0.7 The shortcomings of / ZnO / Ni can promote its advantages, and under the regulation of lignin, the composite material forms a ternary heterojunction structure, which can transfer photogenerated electrons more efficiently, thereby improving the overall reaction rate. In the present invention, lignin is used as an important experimental raw material to promote the high-value utilization of lignin. The process method has the advantages of simplicity, easy availability of raw materials and low cost.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] The present invention uses lignin as a carbon source and a surfactant to change the interfacial energy of water and anhydrous ethanol, thereby improving the mutual self-assembly ability of lignin, Zn and Ni in the liquid; at the same time, the use of an alkaline precipitant can improve the dispersion ability of lignin in the mixed liquid; and in situ formation of lignin-derived carbon / Ni3ZnC during the carbonization process. 0.7 / ZnO / Ni composite material. In the polycrystalline structure, Ni is the center and Ni3ZnC 0.7 The ZnO and ZnO form twin heterojunctions, which improve the electron transport capacity of the composite material during the catalytic process. The interaction between the components enhances the Ni3ZnC 0.7 The stability and 0.7The hydrogen evolution performance of / ZnO / Ni optimizes the photothermal catalytic process; under the carrier effect and support effect of lignin carbon, the ternary structure can remain stable under different photothermal conditions and maintain activity for a long time. At the same time, the composite structure allows for a wider range of light absorption, maximizing the photothermal conversion efficiency. The application of this material in the field of photothermal catalysis, especially in the field of photothermal catalytic hydrogen production, can significantly improve its hydrogen production efficiency, which is conducive to its promotion in industrial applications of sustainable hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 7 0.7 X-ray diffraction patterns of the / ZnO / Ni composite material and the composite material prepared in Comparative Example 1.
[0039] Figure 2 Lignin derived carbon / Ni3ZnC prepared in Example 1 0.7 Scanning electron microscope image of / ZnO / Ni composite material.
[0040] Figure 3 Lignin derived carbon / Ni3ZnC prepared in Example 2 0.7 Scanning electron microscope image of / ZnO / Ni composite material.
[0041] Figure 4 Lignin derived carbon / Ni3ZnC prepared in Example 3 0.7 Scanning electron microscope image of / ZnO / Ni composite material.
[0042] Figure 5 Lignin derived carbon / Ni3ZnC prepared in Example 4 0.7 Scanning electron microscope image of / ZnO / Ni composite material.
[0043] Figure 6 Lignin derived carbon / Ni3ZnC prepared in Example 5 0.7 Scanning electron microscope image of / ZnO / Ni composite material.
[0044] Figure 7 This is a scanning electron microscope image of the composite material prepared in Comparative Example 1.
[0045] Figure 8 Lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 3 0.7 Nitrogen adsorption-desorption isotherms and pore size distribution of / ZnO / Ni composite materials.
[0046] Fig. 9 Lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 3 0.7 Raman spectrum of / ZnO / Ni composite material.
[0047] Fig.10 Lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 3 0.7 Infrared thermal imaging of ZnO / Ni composite material under illumination (500W xenon lamp).
[0048] Fig.11 Lignin derived carbon / Ni3ZnC prepared in Example 1 0.7 Transmission electron microscope image, particle size distribution image, high-magnification transmission electron microscope image and lattice measurement image of / ZnO / Ni composite material.
[0049] Fig.12 Lignin derived carbon / Ni3ZnC prepared in Example 1 0.7 / ZnO / Ni composite material mapping diagram.
[0050] Fig.13 Lignin derived carbon / Ni3ZnC prepared in Example 1 0.7 / ZnO / Ni composite material in ethanol, α-cellulose and ethanol and α-cellulose mixed liquid hydrogen production effect diagram.
[0051] Fig.14 Lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 7 0.7 / ZnO / Ni composite material and the composite material prepared in comparative example 1 in hydrogen production effect in ethanol and α-cellulose mixed liquid. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0053] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0054] Example 1
[0055] 2.0 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 8 mol / L sodium hydroxide solution and 10 ml of 1 mol / L mixed salt solution of zinc nitrate hexahydrate and nickel nitrate hexahydrate were prepared, wherein the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate was 1:1. The mixed salt solution was added to the mixture of alkali lignin and ethanol, and stirred for 10 min. Then, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was then placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was then centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0056] Example 2
[0057] 2.0 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 5 mol / L sodium hydroxide solution, 10 ml of 0.5 mol / L zinc nitrate hexahydrate solution, and 10 ml of 1 mol / L nickel nitrate hexahydrate solution were prepared. The zinc nitrate hexahydrate solution and the nickel nitrate hexahydrate solution were mixed to obtain a mixed salt solution. The mixed salt solution was then added to the mixed solution of alkali lignin and ethanol. After stirring for 10 min, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was then placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was then centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0058] Example 3
[0059] 2.0 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 7 mol / L sodium hydroxide solution, 10 ml of 1 mol / L zinc nitrate hexahydrate solution and 10 ml of 0.5 mol / L nickel nitrate hexahydrate solution were prepared. The zinc nitrate hexahydrate solution and the nickel nitrate hexahydrate solution were mixed to obtain a mixed salt solution. The mixed salt solution was added to the mixed solution of alkali lignin and ethanol. After stirring for 10 min, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0060] Example 4
[0061] 1.5 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 8 mol / L sodium hydroxide solution and 10 ml of 1 mol / L mixed salt solution of zinc nitrate hexahydrate and nickel nitrate hexahydrate were prepared, wherein the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate was 1:1. The mixed salt solution was added to the mixture of alkali lignin and ethanol, and stirred for 10 min. Then, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was then placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was then centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0062] Example 5
[0063] 2.5 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 8 mol / L sodium hydroxide solution and 10 ml of 1 mol / L mixed salt solution of zinc nitrate hexahydrate and nickel nitrate hexahydrate were prepared, wherein the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate was 1:1. The mixed salt solution was added to the mixture of alkali lignin and ethanol, and stirred for 10 min. Then, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was then placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was then centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0064] Example 6
[0065] 2.0 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 8 mol / L sodium hydroxide solution and 10 ml of 1 mol / L mixed salt solution of zinc nitrate hexahydrate and nickel nitrate hexahydrate were prepared, wherein the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate was 1:1. The mixed salt solution was added to the mixture of alkali lignin and ethanol, and stirred for 10 min. Then, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was then placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was then centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 450 ° C at a heating rate of 5 ° C / min in a nitrogen atmosphere and calcined for 3 hours, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0066] Example 7
[0067] 2.0 g of alkali lignin was added to 40 ml of anhydrous ethanol, and magnetically stirred at room temperature for 2 h. Then, 10 ml of 8 mol / L sodium hydroxide solution and 10 ml of 1 mol / L mixed salt solution of zinc nitrate hexahydrate and nickel nitrate hexahydrate were prepared, wherein the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate was 1:1. The mixed salt solution was added to the mixture of alkali lignin and ethanol, and stirred for 10 min. Then, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was placed in a water bath and heated at 90 ° C for 120 min. The reaction mixture was centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0068] Comparative Example 1
[0069] 2.0 g of phthalic acid was added to 40 ml of anhydrous ethanol, and the mixture was stirred magnetically at room temperature for 2 h. Then, 10 ml of 8 mol / L sodium hydroxide solution and 10 ml of 1 mol / L mixed salt solution of zinc nitrate hexahydrate and nickel nitrate hexahydrate were prepared, wherein the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate was 1:1. The mixed salt solution was added to the mixture of alkali lignin and ethanol, and stirred for 10 min. Then, the prepared sodium hydroxide solution was added dropwise, and then 30 ml of water was added. The mixture was placed in a water bath and heated at 80 ° C for 60 min. The reaction mixture was centrifuged, washed with deionized water and anhydrous ethanol for 3 times each, and dried overnight to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni material precursor, and then put the precursor into a tube furnace, heated to 550℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and calcined for 1h, and cooled to room temperature to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite materials.
[0070] Example Effect Description
[0071] The prepared lignin-derived carbon / Ni3ZnC was measured using a Rigaku D / Max-2400 X-ray powder diffractometer according to the test method (10°~80°, 10° / min). 0.7 The crystal structure of the prepared lignin-derived carbon / Ni3ZnC / ZnO / Ni composite material was observed using a Hitachi SU8220 field emission scanning electron microscope. 0.7 The microstructure of the prepared lignin-derived carbon / Ni3ZnC / ZnO / Ni composite material was tested using a Micromeritics ASAP2460 physical adsorption analyzer. 0.7 The specific surface area and pore structure of the prepared lignin-derived carbon / Ni3ZnC / ZnO / Ni composite material were analyzed using LabRAMramis micro-Raman spectrometer. 0.7 Carbonization effect of / ZnO / Ni composites; FLIR T840 infrared thermal imager was used to test the carbonization effect of lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite material photothermal conversion ability; The prepared lignin-derived carbon / Ni3ZnC was observed using a Thermo Fisher Talos F200s transmission electron microscope 0.7 Lattice size and element distribution of / ZnO / Ni composites.
[0072] Table 1 Specific surface area and pore volume of examples
[0073]
[0074] Figure 1 Lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 70.7 X-ray diffraction patterns of the composite material prepared in Example 1 and the composite material prepared in Example 1. It can be seen from the figure that the prepared materials have Ni3ZnC 0.7 The characteristic peaks of ZnO and Ni are shown in Table 1. Due to the different ratios of Ni and Zn in Examples 1 to 3, the crystal strength of the composite materials obtained is also different. When the Zn ratio is higher than that of Ni, the crystal strength of the generated ZnO is better (Example 2); when the Ni ratio is higher than that of Zn, the generated Ni3ZnC 0.7 When the amount of lignin added was 1.5 g (Example 4), the Ni3ZnC 0.7 The crystal form of the phase is the best. It may be that compared with the addition amount of 2g, less lignin will reduce less Ni during calcination, which can promote the conversion of some NiZn alloy into Ni3ZnC 0.7 , so that Ni3ZnC 0.7 The crystal form of the phase is good. The crystal strength of Example 5 is higher than that of Example 1, which may be because too much lignin provides too many loading sites, and a metal catalyst is generated in situ during the calcination process, so that the crystal strength of the material is higher than that of Example 1. The changes in the calcination temperature, reaction time and reaction temperature in Examples 6 and 7 did not significantly change the composition of the composite material. A calcination temperature below 550°C will reduce the strength of the crystal, while correspondingly extending the reaction time and increasing the reaction temperature will increase the crystal strength of the composite material. Comparative Example 1 is a composite material prepared using phthalic acid instead of lignin. It can be seen that the prepared material is composed of ZnO and Ni. This may be because phthalic acid does not have the dispersing effect of lignin during the preparation process, and Ni3ZnC 0.7 Precursor.
[0075] Figures 2 to 6 The SEM images of the materials prepared in Examples 1 to 5 show that Ni3ZnC 0.7 / ZnO / Ni and lignin-derived carbon are in a loading relationship, and lignin carbon provides loading sites for metal catalysts, having a carrier effect, and each composite material lignin-derived carbon prepared in each embodiment has a large amount of metal catalysts on it, indicating that the material can efficiently load catalysts. Figure 7 This is the SEM image of the composite material prepared in Comparative Example 1. From the figure, it can be seen that many metal catalysts are loaded on the carbon carrier generated by calcining phthalic acid, but too much loading may hinder the adsorption of the substrate during the catalytic process and thus affect the catalytic performance. The composite materials prepared in Examples 1 to 5 can see obvious lignin-derived carbon. The biochar can effectively adsorb the substrate to improve the mass transfer efficiency, and can also play an electron buffering role, thereby enhancing the catalytic performance of the composite material.
[0076] Figure 8 The lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 3 0.7 From the pore size distribution diagram and N2 desorption curve diagram of the ZnO / Ni composite material, it can be seen that the material prepared in the embodiment mainly exists in a mesoporous form (as shown in Table 1), and Example 1 has a certain microporous structure, which is beneficial to the adsorption of the substrate. At the same time, the material prepared in Example 1 also has the largest specific surface area; from the N2 desorption curve diagram, it can be seen that the composite material prepared in the embodiment belongs to the classic type IV hysteresis regression line.
[0077] Fig. 9 The lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 3 0.7 Raman spectrum of / ZnO / Ni composite material. It can be seen from the figure that the G peak intensity of the prepared composite material is greater than the D peak, indicating that the degree of graphitization of the composite material is high, and the degree of graphitization of the prepared lignin-derived carbon is good. A higher degree of graphitization can improve the electron transfer, structural stability, selectivity and active site efficiency of the composite material.
[0078] Fig.10 The lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 3 0.7 Infrared thermal imaging of the ZnO / Ni composite material. The composite material was irradiated at a power of 500W by a xenon lamp, and the effect was tested by an infrared thermal imager. It can be seen from the figure that Example 1 can reach 123°C at 152s, and the materials of other examples can also reach above 90°C, indicating that the composite materials prepared in Examples 1 to 3 have good light-to-heat conversion performance.
[0079] Fig.11 and Fig.12 The lignin-derived carbon / Ni3ZnC prepared in Example 1 0.7 The transmission electron microscope image and element distribution diagram of the / ZnO / Ni composite material. It can be seen from the figure that the particle size of the composite material prepared in Example 1 under the transmission electron microscope is about 10.48nm. The high-power transmission electron microscope shows that the lattice fringes at ABC represent ZnO, Ni and Ni3ZnC 0.7 , and these three phases form heterojunctions in pairs, and form a Ni-centered, metallic property of Ni is conducive to the rapid transfer of electrons in the catalytic system. The heterojunction can transfer photogenerated electrons more efficiently, thereby increasing the overall reaction rate. Fig.12 It can be seen that the distribution of Zn, Ni, C, and O in the composite material conforms to the element distribution law of the composite material.
[0080] Fig.13The lignin-derived carbon / Ni3ZnC prepared in Example 1 0.7 / ZnO / Ni composite material hydrogen production performance diagram. As shown in the figure, the prepared material produces hydrogen under the effects of ethanol (50ml 10% volume concentration ethanol aqueous solution, no cellulose), cellulose (50ml, obtained by mixing 0.5g cellulose and pure water as solvent) and ethanol and cellulose mixture (50ml, obtained by mixing 0.5g cellulose and 10% volume concentration ethanol aqueous solution) (reaction temperature is 473K). It can be seen that when the substrate cellulose is 0.5g, neither ethanol nor cellulose alone has a better effect than the combination of the two. Adding an appropriate amount of ethanol to the substrate can enhance the hydrogen evolution effect of the system. The upper right corner is a comparison of the substrate before and after catalysis. It can be seen that the material can completely react cellulose after the reaction is completed.
[0081] Fig.14 The lignin-derived carbon / Ni3ZnC prepared in Examples 1 to 7 0.7 / ZnO / Ni composite material and the hydrogen production performance diagram of the composite material prepared in comparative example 1 (the substrates are all 50ml 0.5g cellulose and 10% ethanol aqueous solution mixed and reacted at 473K for 2 hours). As shown in the figure, the material prepared in Example 1 has the best performance compared with the materials in Examples 2 and 3, thanks to the appropriate ratio of Ni and Zn. However, too high a ratio of Ni and Zn will lead to stronger interaction between Zn-O bonds, thereby limiting electron transfer, resulting in reduced catalytic performance of the composite material and affecting the electron density around NiZn. Unbalanced electron density will destroy the interaction with the reactants, resulting in reduced catalytic effect. In Examples 4 and 5, due to the excessive and insufficient addition of lignin, the catalyst metal composition and the carrier effect of lignin carbon are not obvious enough, resulting in low catalytic performance; in Examples 6 and 7, since the preparation process parameters are roughly the same as those in Example 1, the catalyst structures obtained are also roughly the same, and the hydrogen production performance is similar to that of Example 1; the composite material prepared in comparative example 1 does not contain Ni3ZnC 0.7 phase, while other embodiments consist of Ni3ZnC 0.7 / ZnO / Ni three phases, especially in Example 1, there is a ternary heterojunction to improve the transfer and transmission efficiency of electrons, thereby making the catalyst performance good. Therefore, Comparative Example 1 may have poor catalytic performance because the two phases composed of Ni and ZnO alone do not play a good combination role.
[0082] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high-load lignin-derived carbon / Ni3ZnC 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: The following steps are involved: (1) The lignin alcohol solution and the mixed salt solution of zinc salt and nickel salt are mixed evenly, the precipitant solution is added dropwise, and then water is added, heated for reaction, washed, and dried to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite material precursor; (2) Lignin-derived carbon / Ni3ZnC 0.7 The precursor of the composite material is calcined to obtain lignin-derived carbon / Ni3ZnC 0.7 / ZnO / Ni composite material.
2. A high-load lignin-derived carbon / Ni3ZnC according to claim 1 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: In step (1), the ratio of lignin, zinc salt and nickel salt is 1.5-2.5 g: 5-10 mmol: 5-10 mmol; The molar ratio of the precipitant, the zinc salt and the nickel salt is 5-8:0.5-2:0.5-2.
3. A high-load lignin-derived carbon / Ni3ZnC according to claim 1 or 2 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: In step (1), the ratio of lignin, zinc salt and nickel salt is 2 g: 5-10 mmol: 5-10 mmol; The molar ratio of the precipitant, the zinc salt and the nickel salt is 7-8:0.5-1:0.5-1.
4. A high-load lignin-derived carbon / Ni3ZnC according to claim 1 or 2 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: The heating reaction temperature in step (1) is 60-100° C. and the time is 40-120 min; The calcination temperature in step (2) is 450-550° C. and the calcination time is 1-3 hours; The heating rate of the calcination in step (2) is 1 to 10°C / min.
5. A high-load lignin-derived carbon / Ni3ZnC according to claim 4 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: The heating reaction temperature in step (1) is 80-90° C. and the reaction time is 60-120 min. The calcination temperature in step (2) is 500-550°C, the calcination time is 1-3h, and the heating rate is 3-6°C / min.
6. A high-loaded lignin-derived carbon / Ni3ZnC according to claim 1 or 2 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: The precipitant solution in step (1) is at least one of aqueous ammonia, potassium hydroxide solution and sodium hydroxide solution; the concentration of the precipitant solution is 5 to 9 mol / L; The concentration of the lignin alcohol solution in step (1) is 12.5-62.5 mg / mL; the lignin is at least one of alkali lignin, sulfate lignin, lignin sulfonate and enzymatic lignin; The concentration of the mixed salt solution of zinc salt and nickel salt in step (1) is 0.5-1 mol / L; the zinc salt in step (1) is at least one of zinc nitrate, zinc acetate, zinc carbonate, zinc chloride and zinc oxalate; The nickel salt in step (1) is at least one of zinc nitrate, zinc acetate, zinc carbonate, zinc chloride and zinc oxalate.
7. A high-load lignin-derived carbon / Ni3ZnC according to claim 6 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: The concentration of the precipitant solution in step (1) is 5 to 8 mol / L; The concentration of the lignin alcohol solution in step (1) is 37.5-62.5 mg / mL; The concentration of the mixed salt solution of zinc salt and nickel salt in step (1) is 0.75-1 mol / L.
8. A high-load lignin-derived carbon / Ni3ZnC according to claim 1 or 2 0.7 A method for preparing a / ZnO / Ni ternary heterojunction composite material, characterized in that: The alcohol solvent in the lignin alcohol solution in step (1) is anhydrous ethanol; The volume ratio of the water added in step (1) to the precipitant solution is (0-30):10, and the volume of the water is not 0; The calcination atmosphere in step (2) is at least one of nitrogen, ammonia and air.
9. A high-load lignin-derived carbon / Ni3ZnC prepared by the preparation method according to any one of claims 1 to 8 0.7 / ZnO / Ni ternary heterojunction composite materials.
10. A high-load lignin-derived carbon / Ni3ZnC as claimed in claim 9 0.7 Application of / ZnO / Ni ternary heterojunction composite materials in the field of photothermal catalysis.
Citation Information
Patent Citations
Preparation of nickel-calcium-based composite catalyst and application thereof in biomass catalytic pyrolysis process
CN110227468A
Method and device for preparing hydrogen-rich gas by cracking and reforming biomass tar
CN115404105A
Preparation method of metal-based material-embedded micro-mesoporous carbon composite nanosphere and application method of metal-based material-embedded micro-mesoporous carbon composite nanosphere in lithium-sulfur battery
CN116053464A
Lignin carbon / zinc oxide nano composite material as well as preparation and application thereof
CN117160435A
Alkaline gas-solid phase photo-thermal catalytic reforming alcohol water vapor hydrogen production method
CN118145597A